MENANGANI CABARAN UMAT ISLAM ERA MODEN (Addressing Challenges of Muslims in Modern Era) - Mohd Nor, Mohd Roslan (Journal of Al-Tamaddun, 2011)
In this modern era, Muslims are facing various challenges which need to be addressed. Discussing the challenges is always needed in order to resolve the issues properly instead of becoming cancerous cells in the public life. This paper seeks to explain some of the challenges that are facing by Muslims in Southeast Asia, especially in Malaysia. Hence, This paper discusses the challenges and proposes some solutions accordingly.